ChemInform Abstract: Iron‐Catalyzed Oxidative C—H/C—H Cross‐Coupling Between Electron‐Rich Arenes and Alkenes. Issue 36 (September 2015) - Ma, Yiyang; Zhang, Dongchao; Yan, Zhiyuan; Wang, Mengfan; Bian, Changliang; Gao, Xinlong; Bunel, Emilio E.; Lei, Aiwen
Abstract A novel FeCl3‐catalyzed oxidative cross‐coupling of 1, 3, 5‐trimethoxybenzene as electron‐rich arene with 1, 1, ‐diarylethenes as well as styrenes using DDQ as the oxidant is developed.